Application of the Multi-Objective Optimization By Ratio Analysis (MOORA) Method in the Chili Seed Selection System (Case Study of Asuli Village, East Luwu Towuti District) - Faradilah Ilham, Huryya Zalza (yocto brain, 2023)
Currently chili plants are plants that are needed by the community, these plants can be processed into cooking spices, the food industry and medicines. In East Luwu Regency chili plants are also the main commodity in agriculture, many farmers make chili plants as a business opportunity, but the production of chili plants in East Luwu Regency has decreased, this decrease in production is due to the lack of yields of chili farmers. So that the supply of chili is reduced and can not meet market demand. The lack of yields was caused by farmers using different types of chili seeds because farmers still had difficulty in determining the right type of chili seeds to develop which resulted in chili cultivation failing to harvest. For this reason, a system is needed that can assist farmers in determining chili seeds that are suitable for cultivation in Asuli Village, East Towuti Luwu District. The criteria used in determining the location of the business are harvest time, number of stalks, weight of chilies, altitude and longevity. This study aims to produce a decision support system in recommending the best chili seeds so that they can help farmers increase red chili production among farmers. The method used is the MOORA method, this method was chosen because this method is very simple, stable, and robust, even this method is able to determine goals from conflicting criteria, where criteria can be of beneficial or unfavorable value (cost). In addition, MOORA also has the ability to easily separate subjective elements from an evaluation process into weighted decision criteria that have several decision-making attributes. The results showed that Salo Dua chili seeds were suitable for cultivation in Asuli Village, East Luwu Towuti District